PENINGKATAN PROFESIONAL GURU MELALUI REGULASI KEPEMIMPINAN KEPALA SEKOLAH DI SD IT SALSABILA 2 YOGYAKARTA - Saputra, M. Fachdir; Hamsah, Muhammad; Nurchamidah, Nurchamidah (Risâlah, Jurnal Pendidikan dan Studi Islam, 2021)
Education has an important role in equipping various abilities of students. One of the goals of education which basically leads students to change. This change allows students to live independently, have hope of ability, and strive for the nation and state. All that can be achieved when handled by professional teachers or teachers who have special expertise, according to their profession.This research was qualitative approach with the field research. Research informants are principals for curriculum and teachers. The results of this study are the regulations of scholl principals such as the Theacher Working Group (KKG), holding recitations every Friday, reciting the yellow book specifically for teachers, reciting 1 juice a week, Friday daily evaluation, fingerprinting, making implementation plans. Learning (RPP), motivational Apel, reciting KIBAR, memorizing and murojaah, reciting women’s fiqh. The implementation of the principal’s regulation greatly influences the professional development of teachers.